Understanding Realism in Contemporary International Relations: Beyond the Structural Realist Perspective - Więcławski, Jacek (Nomos Verlagsgesellschaft mbH & Co. KG, 2019)
This book outlines the evolution of the realist paradigm in the study of international relations. It identifies the challenges that realism has faced together with the fall of the bipolar order and the ‘way ahead’ for realism in international reality since the end of the Cold War. The book indicates different realist responses to contemporary international relations. It reveals a competition between systemic-oriented theories and approaches that accept a variety of unit-level variables. Thus, realism faces a clear dilemma about how deeply to reach into the domestic nuances of foreign policymaking and how much of the previous structural and systemic perspective to retain. Realism’s response to this challenge is neither easy nor obvious and has contributed to further tensions inside the realist camp. Dr. Jacek Więcławski studies theories of international relations. He is an assistant professor at the Institute of Political Science at the University of Warmia and Mazury in Olsztyn, Poland.